Experimental benchmarking of Unstructured Transmission Line Modelling (UTLM) method in modelling twisted wires - Meng, Xuesong; Sewell, Phillip; Rahman, Nur H.A.; Vukovic, Ana; Benson, Trevor M. (Applied Computational Electromagneitcs Society, 2016)
In this paper the Unstructured Transmission Line Modelling (UTLM) method based on a tetrahedral mesh has been applied to modelling of the coupling between a single wire and a twisted wire pair. The effects of wire twisting on the crosstalk and coupling between wires are modelled by explicitly meshing wire geometries; simulation results are compared with experimental ones. Excellent agreement between simulated and measured results validates the viability and accuracy of the UTLM method and indicates the potential of the UTLM method for modelling complex wire structures.